Inside Cover: Adaptive Chemoenzymatic Microreactors Composed of Inorganic Nanoparticles and Bioinspired Intrinsically Disordered Proteins (Angew. Chem. Int. Ed. 21/2020). Issue 21 (28th April 2020) - Capasso Palmiero, Umberto; Küffner, Andreas M.; Krumeich, Frank; Faltova, Lenka; Arosio, Paolo
Abstract : Controlled coupling of phase separation and reactions provides a step towards mimicking the ability of cells to conduct a symphony of functions in space and time. In their Communication on page 8138, P. Arosio and co‐workers leverage a class of bio‐inspired intrinsically disordered proteins to generate composite protein–inorganic compartments that couple reversible self‐assembly in response to multiple stimuli with the ability to locally confine chemoenzymatic reactions.